ENHANCING CHILDREN’S LEARNING INTEREST THROUGH READING ACTIVITIES IN CELEBRATION OF THE MISSION AND REFORMATION IN BAWONIFAOSO VILLAGE - Harefa, Darmawan (Haga : Jurnal Pengabdian Kepada Masyarakat, 2025)
This community service program, titled “Enhancing Children’s Learning Interest Through Reading Activities in Celebration of the Mission and Reformation in Bawonifaoso Village”, aimed to improve children’s literacy skills and foster a lifelong interest in reading. The program implemented various reading activities, including interactive storytelling, mobile reading carts, reading corners, and group discussions, integrated with the village’s mission and reformation celebrations to create a culturally relevant and engaging learning environment. Observations and evaluations revealed that children showed increased reading motivation, better comprehension, and higher participation in reading sessions. The program also emphasized the importance of family and community involvement, as parental support and local volunteer participation significantly contributed to the sustainability of the initiative. Despite some challenges, such as limited access to reading materials and variations in parental engagement, the program effectively demonstrated that structured, interactive, and culturally contextualized reading activities could enhance children’s learning interest. The results suggest that combining literacy programs with community engagement and culturally meaningful events can nurture a positive reading culture among children, promoting both academic growth and personal development.